A "Black Body Electric" - African American Rhetoric(s) and the Hip-Hop Aesthetic: Claudia Rankine's Citizen, Beyonce Knowles' Lemonade, and Ta-Nehisi Coates' Between the World and Me - Moore, Nadine (East Carolina University, 2018)
This work examines the formalistic shifts in contemporary African American literature through a hip-hop lens. No longer following the status quo regarding genre or voice, these texts manage to reposition Black writing by forcing an intimate conversation with their readers that compels introspection. Coupled with a mixed-media approach, these works manage to engage and center those readers who might otherwise not have access to the interior monologues of what it feels like to be Black in "post-racial" America.
Keywords: American literature--African American authors; Hip-hop--Influence; Rankine, Claudia, 1963-, Citizen; Beyoncé, 1981-, Lemonade; Coates, Ta-Nehisi. Between the world and me